Jargons Used by Wayang Kamasan Painter Community - Ni Putu Eka Widari (Linguistics Initiative, 2021)
The aim of this study is to find out the languages especially the Jargon used by Wayang Kamasan painter and its meaning. The reason of this researcher was conducted because many people know Wayang Kamasan painting but they rarely know the jargon that is used by painter when they pain Wayang Kamasan. This study used qualitative approach to find out the jargons used by Wayang Kamasan Painter. This research is included phenomenological research because this research described a situation or phenomenon that is the Jargon used by Painter Wayang Kamasan. The method that used to collect the data was observation and interview. The instruments used in this research were interview guide and tape recording. This study conducted in Kamasan village, and the subjects were 10 Wayang Kamasan painter. The result showed that there were 28 jargons used by Wayang Kamasan painter. There were 14 jargons used by Wayang Kamasan painter when they are making the painting. There were also 14 jargons used in the term of tool or equipment that they used in making Wayang Kamasan painting. Through the findings of this research hopefully can help the society know more about jargons used by Wayang Kamasan painter when they make a painting.